Proceedings of the 13th International Conference on Modularity - MODULARITY '14 2014
DOI: 10.1145/2584469.2577086
|View full text |Cite
|
Sign up to set email alerts
|

Assessing modularity using co-change clusters

Abstract: It is widely accepted that traditional modular structures suffer from the dominant decomposition problem. Therefore, to improve current modularity views, it is important to investigate the impact of design decisions concerning modularity in other dimensions, as the evolutionary view. In this paper, we propose the ModularityCheck tool to assess package modularity using co-change clusters, which are sets of classes that usually changed together in the past. Our tool extracts information from version control plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 16 publications
(23 reference statements)
0
18
0
4
Order By: Relevance
“…Artifacts that have changed together appear closer to each other in the layout computed by them. Silva et al [22] considered the co-change graph as a sparse graph and retrieved the co-change clusters of system classes using Chameleon clustering [14]. This direction was further pursued by de Oliviera et al [7] who provided empirical evidence that static dependencies across the modules do not truly capture the future maintenance cost.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Artifacts that have changed together appear closer to each other in the layout computed by them. Silva et al [22] considered the co-change graph as a sparse graph and retrieved the co-change clusters of system classes using Chameleon clustering [14]. This direction was further pursued by de Oliviera et al [7] who provided empirical evidence that static dependencies across the modules do not truly capture the future maintenance cost.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, co-change data can be easily mined from software repositories without analyzing the code-base. This motivated Gall, Hajek and Jazayeri [11], and others [7,22] to define coupling and cohesion in terms of co-change relations. Geipel and Schweitzer [12] and the subsequent work [1,6,19] shows that the nature of the interplay between static dependencies and co-changes is not completely understood although reasonably strong correlation exists between the two.…”
Section: Introductionmentioning
confidence: 99%
“…First, we do not use all changesets when building the graph; and thus we only consider commits explicitly related to at least one issue present in the Issues Tracking System (ISS) of the target systems-since this decision tends to produce clusters that are more semantically related [71]. With regard to the number of issues associated with commits, we found that only 4% of the commits are associated with more than one issue and only 0.7% are associated with more than 2 issues.…”
Section: Extracting Co-change Clustersmentioning
confidence: 99%
“…For the first threshold, we experiment with the value [16] and the value 100-because we grouped entities per issue instead of commit, and this scenario leads to a greater number of associations. For the second threshold, we experiment with the values 1 and 2, also following the recommendations of [16,71]. Finally, for the third threshold, we experiment with the value 0 (according to Silva et al [71]) and with the value 0.5 (a slightly more conservative scenario than the value 0.4 recommended in [16]).…”
Section: Selection Of the Threshold Combinationmentioning
confidence: 99%
See 1 more Smart Citation